Factors Influencing Late Consultation Among Patients with Rectal Bleeding in University Kebangsaan Malaysia Medical Centre - Syahnaz Mohd Hashim; Khairani Omar; Tong Seng Fah; Tuti Iryani Daud; Shamsul Azhar Shah; Ismail Sagap; Mohd Radzniwan A Rashid (Asian Pacific Organization for Cancer Prevention, 2024)
Volume:11 Issue:5